2019
DOI: 10.3389/fnins.2019.00549
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 Alleviates Cognitive Dysfunction in Chronic Cerebral Hypoperfusion Rats by Improving Hemodynamics

Abstract: Compensatory vascular mechanisms can restore cerebral blood flow (CBF) but fail to protect against chronic cerebral hypoperfusion (CCH)-mediated neuronal damage and cognitive impairment. Prostaglandin E1 (PGE1) is known as a vasodilator to protect against ischemic injury in animal models, but its protective role in CCH remains unclear. To determine the effect of PGE1 on cerebral hemodynamics and cognitive functions in CCH, bilateral common carotid artery occlusion (BCCAO) was used to mimic CCH in rats, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…Another previous F-18 FDG PET study in a CCH mouse model revealed that glucose metabolism in the hippocampus, as well as in the cortex, decreased for up to 6 months after applying microcoils to bilateral CCA, but selective vulnerability to ischemia was not detected in the hippocampus [ 33 ]. This may be because the compensation mechanisms for the recovery of CBF were not more extensive in mice than in rats, and the sustained decrease in CBF in the cortex affected the decrease in cerebral glucose metabolism [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another previous F-18 FDG PET study in a CCH mouse model revealed that glucose metabolism in the hippocampus, as well as in the cortex, decreased for up to 6 months after applying microcoils to bilateral CCA, but selective vulnerability to ischemia was not detected in the hippocampus [ 33 ]. This may be because the compensation mechanisms for the recovery of CBF were not more extensive in mice than in rats, and the sustained decrease in CBF in the cortex affected the decrease in cerebral glucose metabolism [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PGE1 on cytoprotection has been widely reported in preclinical models, but the underlying molecular mechanism needs to be clarified (42,43). Combined with lithium, PGE1 exerted significant roles in a rat cerebral ischemia model (12). Moreover, PGE1 is also reported to prevent neuronal apoptosis in the superficial dorsal horn following chronic constriction of the sciatic nerve in rats (17).…”
Section: Discussionmentioning
confidence: 99%
“…For the therapy of patients with peripheral arterial occlusive disease, PGE1 has played broad roles in clinical practices (9,10). Clinical and pre-clinical evidence showed the benefits of PGE1 on curing ischemic heart disease and cerebral ischemia (8,(11)(12)(13). We have previously tried to use PGE1 to treat ICH patients in the clinic and have achieved positive protective results (14).…”
Section: Introductionmentioning
confidence: 99%
“…In the other nine cases, the most common carotid arteries (CCAs) were operated for inducing cerebral hypoperfusion (9/13). Five studies conducted suture ligation, (Ouchi et al, 1998;Ohmori et al, 2011;Kitamura et al, 2012;Park et al, 2019;Xie et al, 2019) and four studies used micro-coils with an inner diameter of 0.18 mm (Shibata et al, 2004;Nishio et al, 2010;Patel et al, 2017;Dominguez et al, 2018). One study used facial vein ligation with sutures for inducing cerebral hypoperfusion (Chen et al, 2009).…”
Section: Study Selectionmentioning
confidence: 99%